Genotyping live fish larvae: Non-lethal and noninvasive DNA isolation from 3–5 day old hatchlings - G. Janelle Espinoza; J. Michael Poland; Jaime R. Alvarado Bremer (BioTechniques)
Genotyping fish larvae is a valuable technique for numerous fields of study. While methods for collecting DNA from early stage larvae have been published, a non-lethal, non-invasive genotyping protocol for hatchlings that is amenable to high-throughput approaches is desirable. Here, we describe a method to individually genotype live, free-swimming, early fish larvae by characterizing their environmental DNA (eDNA). We demonstrate the utility of the method by assigning parentage to a sample (n = 50) of 3–5-day-old sheepshead minnow (Cyprinodon variegatus) larvae hatchlings, with very high rates of genotyping success (98%) and survival (92%) using mitochondrial and microsatellite DNA data. This method could be easily adapted to characterize early fish larvae from other model and non-model fish species, such as Danio rerio (zebrafish) and Medaka medaka.